2022
DOI: 10.2147/jir.s374060
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship and Sequencing of Interleukins4, 13, 31, and 33 – An Integrated Systematic Review: Dermatological and Multidisciplinary Perspectives

Abstract: The interrelations and sequencing of interleukins are complex (inter)actions where each interleukin can stimulate the secretion of its preceding interleukin. In this paper, we attempt to summarize the currently known roles of IL-4, IL-13, IL-31, and IL-33 from a multi-disciplinary perspective. In order to conduct a comprehensive review of the current literature, a search was conducted using PubMed, Google Scholar, Medscape, UpToDate, and Key Elsevier for keywords. The results were compiled from case reports, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 186 publications
0
8
0
Order By: Relevance
“…Prasad and Abcarian documented the neoplastic change in anal condyloma to 1.82%, with four cases exhibiting both histological and invasive characteristics, while only two cases displayed significant infiltration into nearby soft tissues without histological indications of malignancy [ 12 , 13 , 14 ]. When squamous cell carcinoma occurs in the context of giant condyloma acuminata, management must be chosen by a multidisciplinary team, and there are some cases when only palliative measures can be offered [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prasad and Abcarian documented the neoplastic change in anal condyloma to 1.82%, with four cases exhibiting both histological and invasive characteristics, while only two cases displayed significant infiltration into nearby soft tissues without histological indications of malignancy [ 12 , 13 , 14 ]. When squamous cell carcinoma occurs in the context of giant condyloma acuminata, management must be chosen by a multidisciplinary team, and there are some cases when only palliative measures can be offered [ 15 , 16 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the viral replicative phase, IL6 secretion increases, which can induce vascular endothelial growth factor and neoplastic proliferation [ 25 ]. Infections with HHV8 viruses are associated with a disturbance of the regulation of the expression of oncogenic and onco-suppressive genes, favored by immunosuppression and cellular activation during the evolution of HIV [ 9 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A heterodimeric receptor complex made up of the oncostatin M receptor beta (OSMRβ) and the IL-31 receptor alpha (Il-31RA) is responsible for transmitting the IL-31 signal [ 135 ]. When the IL-31 receptor is activated, either directly or indirectly, at least four signaling pathways—AKT/PI3K, JAK-STAT, MAPK (ERK1/2, p38, JNK), and NF-kB—are activated in a cell-dependent manner [ 135 , 136 , 137 , 138 , 139 ]. IL-31 activity in keratinocytes is mostly regulated by STAT3 phosphorylation, while various IL-31RA isoforms may have an impact on this activity [ 136 ].…”
Section: Histamine-independent Pruritogensmentioning
confidence: 99%
“…Studies have shown that IL-31 is overexpression in transgenic mice causes primary alopecia, severe pruritus, and peripheral lymphadenopathy independent of mast cells [ 135 ]. Upregulation of IL-31 has been shown to cause an atopic dermatitis-like phenotype in mouse models [ 137 ].…”
Section: Histamine-independent Pruritogensmentioning
confidence: 99%